2022
DOI: 10.3390/ani12223193
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Se-Enriched Cardamine enshiensis Supplementation Alleviates Transport-Stress-Induced Body Weight Loss, Anti-Oxidative Capacity and Meat Quality Impairments of Broilers

Abstract: The aim of this experiment was to explore the effects of a new selenium (Se) source from Se-enriched Cardamine enshiensis (SeCe) on body weight loss, anti-oxidative capacity and meat quality of broilers under transport stress. A total of 240 one-day-old ROSS 308 broilers were allotted into four treatments with six replicate cages and 10 birds per cage using a 2 × 2 factorial design. The four groups were as follows: (1) Na2SeO3-NTS group, dietary 0.3 mg/kg Se from Na2SeO3 without transport stress, (2) SeCe-NTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…Similarly, the glucose levels demonstrated an interactive effect between crate density and weather conditions in the current investigation wherein broilers transported in high-density crates during hot weather displayed elevated glucose levels, and conversely, those in low-density crates during cold weather also manifested increased glucose levels. The body weight losses followed a similar pattern to the stress markers cortisol and glucose, suggesting a potential association with stress [29]. In contrast to our findings, the research by [20] reported that broilers subjected to high transport density exhibited elevated glucose levels compared to those with low transport density…”
Section: Discussioncontrasting
confidence: 53%
“…Similarly, the glucose levels demonstrated an interactive effect between crate density and weather conditions in the current investigation wherein broilers transported in high-density crates during hot weather displayed elevated glucose levels, and conversely, those in low-density crates during cold weather also manifested increased glucose levels. The body weight losses followed a similar pattern to the stress markers cortisol and glucose, suggesting a potential association with stress [29]. In contrast to our findings, the research by [20] reported that broilers subjected to high transport density exhibited elevated glucose levels compared to those with low transport density…”
Section: Discussioncontrasting
confidence: 53%
“…Also, the biogenic SeNPs could enhance Se bioactivity through nanoscale effects to promote the antioxidant properties [41]. Se is a key component of Se-containing proteins and enzymes, such as GSH-Px [42,43], which play a crucial role in the antioxidant defense system [44]. It has been reported that dietary Se enhanced the GPx activity of muscle, which contributed to the improvement of meat quality [45].…”
Section: Discussionmentioning
confidence: 99%